التّفاعل السّردي في القصيدة الجزائريّة القديمة أبو حمو موسى الزياني أنموذجا - عرفة ثروة; حماده سعد (My University, 2025)
التّفاعل السّردي قائم على فكرة (الدّوائر البنيويّة) في القصيدة، من خلال سعي السّارد إلى خلق حركة مقابلة بين الفعل وردّ الفعل التّلقائي أو المصنوع؛ حيث يعتمد الرّاوي على ذاته أو ذوات يصطنعها من أجل حدوث التّفاعل بين الذّوات، وبين الأفعال، بما يلائمه من ردود فعل، هذا النّوع من التّفاعل الذّاتي يحتاج أحيانا إلى متلقٍ نصيٍّ يمثّل صورة من الصّور الّتي يقدّمها السّارد للقصيدة. ومن هنا يأتي هذا البحث المتوسّل بالمنهج البنيويّ في السّرد بما فيه من تصوّرات عن دور السّارد، ودور الذّوات الأخرى، والتّصوّرات الزّمانيّة بين اليقينيّة والظّنيّة، وكيفيّة حدوث التّفاعل بين الشّاعر/السّارد وبين محتوى السّرد بالصّورة التّي تجعل السّرد جامعًا لعناصر وجوده مثل الفّعل ثم ردّ الفعل، بل محاولة تجاوز هذا السّرد بما يجعل السّارد يقدّم المتلقّي الّذي هو من صنعه، فإلى أيّ مدى نجح أبو موسى في تحقيق التّفاعل السّردي -وفق هذا التّصوّر- في قصائده؟ وبأيّ الأشكال؟ The narrative interaction is based on the poem’s idea of structural circles, in which the narrator attempts to create a reciprocal movement between the action and the automatic or manufactured reaction. The narrator relies on the self or selves he fabricates in order to achieve interaction between the selves and the actions, with suitable reactions. This type of self-interaction sometimes requires a textual recipient that represents an image from those presented by the narrator to the poem. Hence comes this research that relies on the structural method in narration, with its conceptions about the role of the narrator, the roles of other selves, the temporal conceptions between certainty and speculation, and how the interaction occurs between the poet/narrator and the narrative content in a way that makes the narrative a collector of its existential elements like action and reaction, but also attempting to surpass this narrative by having the narrator present the recipient who is his creation. To what extent did Abu Musa succeed in achieving narrative interaction according to this conception in his poems, and in what forms?
مقال . القارئ للدراسات الأدبية و النقدية و اللغوية. مج 08. ع 01
Keywords: التفاعل السّردي; حركة مقابلة; الذّوات; الأفعال; ردود الفعل; المتلقّي